Variability in Sulfur Isotope Records of Phanerozoic Seawater Sulfate. Issue 18 (17th September 2020) - Present, Theodore M.; Adkins, Jess F.; Fischer, Woodward W.
Abstract: The δ 34 S of seawater sulfate reflects processes operating at the nexus of sulfur, carbon, and oxygen cycles. However, knowledge of past seawater sulfate δ 34 S values must be derived from proxy materials that are impacted differently by depositional and postdepositional processes. We produced new time series estimates for the δ 34 S value of seawater sulfate by combining 6, 710 published data from three sedimentary archives—marine barite, evaporites, and carbonate‐associated sulfate—with updated age constraints on the deposits. Robust features in multiple records capture temporal trends in the δ 34 S value of seawater and its interplay with other Phanerozoic geochemical and stratigraphic trends. However, high‐frequency discordances indicate that each record is differentially prone to depositional biases and diagenetic overprints. The amount of noise, quantified from the variograms of each record, increases with age for all δ 34 S proxies, indicating that postdepositional processes obscure detailed knowledge of seawater sulfate's δ 34 S value deeper in time. Plain Language Summary: Sedimentary rocks deposited in ancient marine basins preserve a record of seawater composition. We compare the sulfur isotopic composition of three sedimentary materials that contain sulfate—a major ion in seawater important for carbon and oxygen cycling. Evaporite salts, the mineral barite, and trace sulfate in limestone each reveal the same first‐order trends over the last 541 × 10 6 years and also display substantial shorter‐order discrepancies that reflect how the materials capture and store paleooceanographic information. These discrepancies partially obscure understanding of the relationship between life, ocean chemistry, and climate. Key Points: The 6, 710 measurements of δ 34 S of sulfate in Phanerozoic sedimentary rocks were compiled and systematically updated to a consistent timescale Records derived from evaporites, barite, and carbonate‐associated sulfate are similar and also contain dramatic short‐term discrepancies Variation created by diagenetic and depositional processes increases with age in all records, obscuring temporal trends in marine sulfate